Nursing Approach According to Roy Adaptation Model in a Patient with Implant-able Cardioverter Defibrillator (ICD) - Aydogdu, Ozlem (Galenos Publ House, 2021)
The nursing profession is a professional health discipline based on philosophy, practice, and research enriched with various models and theories. This discipline develops knowledge and provides a special perspective to its practices using models and theories when planning and maintaining the care of individuals. The professionalism of the nursing profession depends on how strong its theoretical structure is and how much the theoretical structure is reflected in nursing practices. The use of nursing care models created in this direction ensures the fulfillment of nursing care in a holistic and systematic manner and also guides nurses. In this article, we present a nursing approach prepared by using the North American Nursing Diagnosis Association I diagnostic system within the scope of Roy's adaptation models of a patient with an implantable cardioverter defibrillator who was followed up in the cardiology clinic.
Keywords: Nursing theory; nursing diagnosis; psychosocial care